2009
DOI: 10.1021/tx900215u
|View full text |Cite
|
Sign up to set email alerts
|

Human Liver Microsome-Mediated Metabolism of Brominated Diphenyl Ethers 47, 99, and 153 and Identification of Their Major Metabolites

Abstract: While the metabolism and excretion of polybrominated diphenyl ethers (PBDEs) have been reported in rodents, PBDE metabolism in humans has only recently been investigated. In this present study, individual human liver microsomes were incubated for 120 min with radiolabeled and nonradiolabeled BDE 47, 99, or 153 to determine their relative degrees of metabolism and to identify the structures of metabolites formed. Radiolabeled samples were analyzed using high-performance liquid chromatography/radiochemical detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 37 publications
1
53
0
1
Order By: Relevance
“…The UPLC/MS method was successfully applied to identify and quantify formation of hydroxy metabolites of BDE-99 by rat liver microsomes in a time-and protein-dependent manner rather than monitoring depletion of BDE-99 [22]. The experimental conditions used, which involved a relatively small amount of liver microsomal protein and short incubation times, suggest that our method is more metabolically responsive compared to previous in vitro investigations of BDE-99 metabolism [26]. The UPLC/MS method will now be applied to further characterize the oxidative metabolism of BDE-99 by determining the kinetic parameters of hydroxy metabolite formation and identifying the cytochrome P450 enzymes involved.…”
Section: Resultsmentioning
confidence: 99%
“…The UPLC/MS method was successfully applied to identify and quantify formation of hydroxy metabolites of BDE-99 by rat liver microsomes in a time-and protein-dependent manner rather than monitoring depletion of BDE-99 [22]. The experimental conditions used, which involved a relatively small amount of liver microsomal protein and short incubation times, suggest that our method is more metabolically responsive compared to previous in vitro investigations of BDE-99 metabolism [26]. The UPLC/MS method will now be applied to further characterize the oxidative metabolism of BDE-99 by determining the kinetic parameters of hydroxy metabolite formation and identifying the cytochrome P450 enzymes involved.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, dihydroxy-BDE-47, 2,4-dibromophenol, dihydroxylated BDE-99 and 2,4,5-tribromophenol have been reported as major metabolites of BDE-47 and BDE-99, respectively, in human liver microsomes (Lupton et al, 2009). Importantly, Kojima et al (2009) found potent antiandrogenic activities of hydroxy-and methoxy-metabolites of PBDEs at nanomolar concentrations, suggesting the involvement of these metabolites in reported toxic modes of action of PBDEs.…”
Section: Comparison Of In Vitro Toxic Potencies Of Pbdesmentioning
confidence: 93%
“…Recently, Lupton et al (2009) showed that BDE-47 was metabolized by human liver microsomes with relatively large interindividual differences. Two metabolites were identified: a dihydroxylated BDE-47 and 2,4-dibromophenol.…”
Section: Bde-47mentioning
confidence: 99%
“…For infants and toddlers, the lactation period encompasses most of the neurodevelopmental period, and breast milk is the predominant source of PBDEs in this population. BDE-153, the predominant congener in human milk from China, Asia and in most of the world (Haraguchi et al, 2009;Ingelido et al, 2007Schecter et al, 2010She et al, 2007Zhao et al, 2010), cannot be metabolized and detoxified by liver microsomes in humans and animals, and it exhibits a high level of bioaccumulation and affinity to brain tissue (Lupton et al, 2009;Staskal et al, 2006). Moreover, the PBDE congener pattern has shifted from BDE-47 and BDE-99 to BDE-153 since the 1980s (Simpson et al, 1981Koh et al, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…BDE-153 exhibits a higher bioaccumulation in human beings (Lupton et al, 2009), a higher bioaccumulation in infants than in adults (Toms et al, 2008), and a higher bioaccumulation and affinity binding to brain tissue than the other congeners. The concentration of BDE-153 is much higher in lipophilic tissues and breast milk than those of BDE-100, BDE-99 and BDE-47 (Staskal et al, 2006), and this concentration in breast milk is positively dependent on the maternal age (Haraguchi et al, 2009Kim et al, 2012Koh et al, 2010.…”
Section: Introductionmentioning
confidence: 97%